Japanese animation : East Asian perspectives - Yokota, Masao, 1954-; Hu, Tze-yue G. (University Press of Mississippi, 2013)
"Japanese Animation: East Asian Perspectives makes available for the first time to English readership a selection of viewpoints from media practitioners, designers, educators, and scholars working in the East Asian Pacific. This collection not only engages a multidisciplinary approach in understanding the subject of Japanese animation but also shows ways to research, teach, and more fully explore this multidimensional world. Presented in six sections, the translated essays cross-reference each other. The collection adopts a wide range of critical, historical, practical, and experimental approaches. This variety provides a creative and fascinating edge for both specialist and nonspecialist readers. Contributors' works share a common relevance, interest, and involvement despite their regional considerations and the different modes of analysis demonstrated. They form a composite of teaching and research ideas on Japanese animation"--